Diterpenes from buds of Wikstroemia chamaedaphne showing anti-hepatitis B virus activities. (July 2018) - Li, Shi-Fei; Jiao, Ying-Ying; Zhang, Zhi-Qiang; Chao, Jian-Bin; Jia, Jie; Shi, Xun-Long; Zhang, Li-Wei
Abstract: Phytochemical study of the buds of Wikstroemia chamaedaphne Meisn. led to the isolation of seven previously undescribed diterpenes, including one tigliane diterpene (wikstchalide A), two daphnane diterpenes (wikstroelides W-X), and four lathyrane diterpenes (laurifoliosides A-B and 2- epi -laurifoliosides A-B), along with four known diterpenes. The structures of these compounds were established by extensive spectroscopic evidence and electronic circular dichroism (ECD) calculations. Wikstchalide A possesses a 5, 6-epoxy ring in the tigliane skeleton. Two compounds exhibited potential anti-hepatitis B virus activities, with IC50 values of 46.5 and 88.3 μg/mL against hepatitis B virus (HBV) surface antigen (HBsAg), and six compounds showed certain inhibitory effects on HBV-DNA replication with the inhibition ratios ranging from 2.0% to 33.0% at the concentrations ranging from 0.39 to 6.25 μg/mL. Graphical abstract: Eleven diterpenes were isolated from buds of Wikstroemia chamaedaphne Meisn., a common herb in China. Some compounds showed certain anti-HBV activities. Highlights: Seven previously undescribed diterpenes were obtained from buds of W. chamaedaphne. ECD calculations were used to confirm the absolute stereochemistry. Wikstchalide A possesses a 5, 6-epoxy ring in the tigliane skeleton. Two compounds exhibited potential against HBV surface antigen activities. Six compounds showed certain inhibitory effects on HBV-DNA replication.